The impact of statin therapy on plasma levels of von Willebrand factor antigen - Sahebkar, Amirhossein; Serban, Corina; Ursoniu, Sorin; Mikhailidis, Dimitri P.; Undas, Anetta; Lip, Gregory Y. H.; Bittner, Vera; Ray, Kausik K.; Watts, Gerald F.; Hovingh, G. Kees; Rysz, Jacek; Kastelein, John J. P.; Banach, Maciej; Lipid and Blood Pressure Meta-analysis Collaboration (LBPMC) Group (Thrombosis and Haemostasis, 2016)
Increased plasma levels of von Willebrand factor antigen (vWF:Ag) are associated with high risk of coronary artery disease. The effect of statin therapy on vWF:Ag levels remains uncertain. Therefore the aim of this meta-analysis was to evaluate the effect of statin therapy on vWF:Ag Levels. A systematic multiple-database search was carried out to identify randomized controlled trials (RCTs) that investigated the effect of statins on plasma vWF:Ag levels. Random-effect meta-analysis of 21 treatment arms revealed a significant decrease in plasma vWF:Ag levels following statin therapy (SMD: −0.54, 95 %CI: −0.87, −0.21, p=0.001). In subgroup analyses, the greatest effect was observed with simvastatin (SMD: −1.54, 95 %CI: −2.92, −0.17, p=0.028) and pravastatin (SMD: −0.61, 95 %CI: −1.18, −0.04, p=0.035), but not with fluvastatin (SMD: −0.34, 95 %CI: −0.69, 0.02, p=0.065), atorvastatin (SMD: −0.23, 95 %CI: −0.57, 0.11, p=0.179) and rosuvastatin (SMD: −0.20, 95 %CI: −0.71, 0.30, p=0.431). The lowering effect of statins on plasma vWF:Ag levels was greater in the subset of studies lasting ≥ 12 weeks (SMD: −0.70, 95 %CI: −1.19, −0.22, p=0.005) compared with that of studies lasting > 12 weeks (SMD: −0.34, 95 %CI: −0.67, 0.003, p=0.052). Finally, low-intensity statin therapy was not associated with a significant reduction in vWF:Ag levels (SMD: −0.28, 95 %CI: −0.82, 0.27, p=0.320), but a significant effect was observed in high-intensity statin trials (SMD: −0.66, 95 %CI: −1.07, −0.24, p=0.002). This meta-analysis of available RCTs demonstrates a significant reduction in plasma vWF:Ag levels following statin therapy.Note: The review process for this manuscript was fully handled by Christian Weber, Editor in Chief.
Keywords: von Willebrand Antigen; statins; cardiovascular diseases; atherosclerosis; thrombosis